2011
DOI: 10.1016/j.neulet.2010.12.010
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol-induced increases in extracellular dopamine are blunted in brain-derived neurotrophic factor heterozygous mice

Abstract: Drugs of abuse like ethanol have the ability to stimulate forebrain dopaminergic pathways. Although the positive reinforcing properties of abused substances are largely attributed to their effects on dopamine transmission, alcohol addiction involves complex interactions between numerous molecular mediators. Brain-derived neurotrophic factor (BDNF) is suggested to have a protective role in regulating the reinforcing effects of ethanol. In the present study, we evaluated the effects of an acute, systemic injecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…Neurotrophins can modulate neuroadaptations in addictive behavior and alcohol consumption is influenced by the interaction between BDNF and dopamine (DA) transmission (Bosse & Mathews ). It has been shown that EtOH exposure in sire mice may induce ADHD‐like (attention deficit hyperactivity disorder) effects such as hyperactive, inattentive and impulsive behaviors in the offspring (Kim et al .…”
Section: Discussionmentioning
confidence: 99%
“…Neurotrophins can modulate neuroadaptations in addictive behavior and alcohol consumption is influenced by the interaction between BDNF and dopamine (DA) transmission (Bosse & Mathews ). It has been shown that EtOH exposure in sire mice may induce ADHD‐like (attention deficit hyperactivity disorder) effects such as hyperactive, inattentive and impulsive behaviors in the offspring (Kim et al .…”
Section: Discussionmentioning
confidence: 99%
“…Ethanol-induced modifications of gene expression in reward-associated brain regions are considered to contribute to long-lasting neuroadaptations and behavioral abnormalities (Lewohl et al, 2000;Kerns & Miles, 2008;Piechota et al, 2010). In addition, extensive research has implicated BDNF neurotransmission in the regulation of responses to drug-related behavioral consequences in general (for review, see for example Corominas et al, 2007;Thomas et al, 2008;Dietz et al, 2009;Ghitza et al, 2010) and ethanol in particular (McGough et al, 2004;Davis, 2008;Bosse & Mathews, 2011). How BDNF may contribute to the rewarding properties of alcohol is not yet known, but it has been shown that exposure to ethanol alters BDNF expression in several brain regions.…”
Section: Discussionmentioning
confidence: 99%
“…Following centrifugation, the supernatant was isolated and stored at −80 °C. BDNF protein was quantified using an ELISA (Promega E max Immunoassay; Madison, WI) according to kit instructions and as detailed in (Bosse & Mathews, 2011; Szapacs et al, 2004). Samples and standards were run in triplicate in Greiner Bio-One High Binding Flat Bottom 96-well microplates.…”
Section: Methodsmentioning
confidence: 99%